Management of rheumatoid arthritis during pregnancy: challenges and solutions - Krause ML (Dove Medical Press, 2016)
Megan L Krause, Ashima Makol Division of Rheumatology, Department of Internal Medicine, Mayo Clinic, MN, USA Abstract: Rheumatoid arthritis, a chronic inflammatory autoimmune disease with significant physical disability, affects women three times more frequently than men, often in their childbearing years. Parenthood decisions can be challenging, often affected by perceptions of their disease state, health care needs, and complex pharmacological treatments. Many women struggle to find adequate information to guide them on pregnancy planning, lactation, and early parenting in relation to their chronic condition. The expanded availability and choice of pharmacotherapies have supported optimal disease control prior to conception and enhanced physical capabilities for women to successfully overcome the challenges of raising children but require a detailed understanding of their risks and safety in the setting of pregnancy and breastfeeding. This review outlines the various situational challenges faced by rheumatologists in providing care to men and women in the reproductive age group interested in starting a family. Up to date evidence-based solutions particularly focusing on the safe use of disease-modifying antirheumatic drugs and biologic response modifiers to assist rheumatologists in the care of pregnant and lactating women with RA are reviewed. Keywords: rheumatoid arthritis, pregnancy, biologics, DMARDs